Songs of the Ketu cult of Bahia (transcriptions) - Merriam, Alan P. (International Library of African Music, 1957)
The transcriptions printed here refer to the article by Dr. Alan P. Merriam on pages 53-67 of the previous edition of the fournal (No. 3). The Editor regrets that owing to a misunderstanding they were not printed together with the article at the time. Notes referring to the transcriptions will be found on page 67 of Journal Vol. I, No. 3.
Keywords: African Music